机器人工作空间边界点提取算法研究与改进 - 陈是扦; 刁燕; 罗华; 李宁波; 钟悦 (Jixie chuandong)
Extracting workspace boundary points is a key link in workspace analysis of robot.The limitations of the existing algorithms for workspace boundary extraction are discussed in detail.Aiming at the inhomogeneity of the boundary points and the difficulty of the inner boundary point extraction with the method of partitioning by rows,a new boundary extraction algorithm of partitioning by angle is presented.The method of combining partitioning by rows method with the local coordinate method is employed to extract the workspace boundary for the low computing efficiency of using local coordinate method alone.The least square method is applied to analyze the performance of different algorithms and the experiment results show that the improved algorithm can achieve better performance in efficiency and accuracy.Finally the workspace boundary points of a surgical robot with redundant degrees of freedom are obtained with the improved algorithm,which proves the validity and feasibility of this algorithm.